THE CRITICAL DISCOURSE ANALYSIS ON THE FAME OF OREO WONDERFILLED ADVERTISEMENT” - Alfriani Ndandara; Frederika Mei Anggraeni (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2019)
Advertisement is one of functional texts which functions to commerce the audience about a product the company sells. A text in the advertisement is considered to contribute people’s intention. This paper conducts a critical analysis on the fame of a product which becomes remarkable since it rises until now, Oreo. Fairclough’s three dimensional frameworks, Gee’s seven building tasks, and Halliday’s functional grammar are employed to do the research. Therefore, this paper discusses the linguistic features, advertisement invention, semiotic aspects, and social contexts. However, the result of the research shows that, the language used in Oreo Wonderfilled advertisement has relation to power. Thus, the advertisement of Oreo does not only attract consumer but also shape the costumers’ mind through the language used both its’ audio or visual. The representation of symbolic power to capture the hearts and minds of consumers is by means of visual, audio, and verbal signs, which are analyzed using semiotics feature.